PERUBAHAN KEBIJAKAN UJIAN NASIONAL (STUDI PELAKSANAAN UJIAN NASIONAL 2015) - Alawiyah, Faridah (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2015)
The change of government in 2014 was followed by changes in education policy. One of the changes in educational policy is the rule of the National Exam. Some of these changes include: UN 2015 will no longer be the only graduation requirements; expansion of the UN text printing; Computer Based Test implementation; and the assessment of UN Integrity. This article will study the policy change of National Examination (UN) in 2015, both in the implementation, objectives, and results. By using the methods of literary study it was found that the implementation of the UN in 2015 turned out to be the average score of the UN 2015 did not change significantly, but the UN Integrity Index showed a bad portrait of education in Indonesia.